1980
DOI: 10.1002/1097-0142(19801201)46:11<2416::aid-cncr2820461120>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-mediated enhancement of lymphocyte response to mitogens in healthy subjects and lung cancer patients

Abstract: Indomethacin (prostaglandin synthetase inhibitor) was found to be capable of enhancing the mitogen-induced lymphocyte proliferative responses of healthy subjects and patients with lung cancer. A whole-blood culture technique was used. Indomethacin had no mitogenic activity. We observed a greater enhancement of lymphocyte response by indomethacin in weak responders as compared with strong responders in healthy subjects and lung cancer patients. A greater enhancement was also noted in lung cancer patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 11 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Previous studies demonstrated that normal human monocytes suppressed either the phytohemagglutinin (PHA) or antigen-induced lymphocytes proliferative response when the monocyte-lymphocyte ratio was increased [50]. Also, human monocytes could be stimulated to secrete large amounts of prostaglandins in vitro , which have been shown to inhibit mitogen-induced lymphocyte response, resulting in suppressing the anti-cancer immunity in various cancers [51], [52], [53]. Therefore, these might be the possible explanations that either an elevated lymphocyte count or depressed monocyte count was favorable prognostic predictor in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that normal human monocytes suppressed either the phytohemagglutinin (PHA) or antigen-induced lymphocytes proliferative response when the monocyte-lymphocyte ratio was increased [50]. Also, human monocytes could be stimulated to secrete large amounts of prostaglandins in vitro , which have been shown to inhibit mitogen-induced lymphocyte response, resulting in suppressing the anti-cancer immunity in various cancers [51], [52], [53]. Therefore, these might be the possible explanations that either an elevated lymphocyte count or depressed monocyte count was favorable prognostic predictor in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of PGE2 have been shown to suppress immune surveillance (181)(182)(183) and to impair killing of malignant cells (184,185). These effects appear to be specific to PGE2 since other eicosanoids have not been shown to have a clear role in the regulation of cellular and humoral immune responses (186).…”
Section: Immune Modulationmentioning
confidence: 99%
“…In support of a suppressive effect of PGE2 is the observation that drugs that inhibit PG synthesis enhance immune responses (184)(185)(186). PGE2 can regulate immune function by acting as a negative feedback inhibitor for such processes as T cell proliferation, lymphokine production and cytotoxicity and for macrophage and natural killer cell cytotoxicity (183,187). Since the growth of various tumors is associated with immune suppression in animals and humans (181,188), inhibition of COX may reduce tumorigenesis.…”
Section: Immune Modulationmentioning
confidence: 99%
“…46 Indomethacin was also found to improve T-cell cell responses to antigen stimulation in patient with melanoma or lung cancer. 47,48 Studies by Lang et al, have shown that use of the selective Cox-2 inhibitor, Rofecoxib, improved monocyte migration and function to levels seen in healthy controls. 49 Other studies have shown that use of selective Cox-2 inhibitors as chemopreventative agents reduces the expansion of immature myeloid suppressor cells.…”
Section: Discussionmentioning
confidence: 99%